2024
DOI: 10.1039/d3na01154b
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial coatings based on amine-terminated graphene oxide and Nafion with remarkable thermal resistance

Mohammed Suleman Beg,
Ella Nicole Gibbons,
Spyridon Gavalas
et al.

Abstract: Nafion and amine-terminated graphene oxide (GO–NH2) coatings inhibit bacterial growth by 99% and this performance is maintained upon thermal annealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Carbon nanotubes and graphene-based polymer nanomaterials exhibit a series of attractive characteristics related to their mechanical, electrical, thermal, sensing and antimicrobial properties [ 56 , 57 , 58 ], although achieving a high level of dispersion is often challenging. Hong et al [ 59 ] demonstrated the in situ growth of CNT on Teflon and polycarbonate (PC) when the polymeric substrates were painted with the catalyst cobalt naphthenate and a mixture of C 2 H 2 (key building block) and H 2 S (sulphur has a promoter role via softening the metal catalyst) was introduced under microwave irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon nanotubes and graphene-based polymer nanomaterials exhibit a series of attractive characteristics related to their mechanical, electrical, thermal, sensing and antimicrobial properties [ 56 , 57 , 58 ], although achieving a high level of dispersion is often challenging. Hong et al [ 59 ] demonstrated the in situ growth of CNT on Teflon and polycarbonate (PC) when the polymeric substrates were painted with the catalyst cobalt naphthenate and a mixture of C 2 H 2 (key building block) and H 2 S (sulphur has a promoter role via softening the metal catalyst) was introduced under microwave irradiation.…”
Section: Discussionmentioning
confidence: 99%